Update on Fertility Preservation - Kaluarachchi, A. (Faculty of Medicine, University of Colombo, 2020)
Fertility preservation has become an important aspect of infertility management. It is particularly important in the management of malignancies in young patients. This is important, particularly in breast cancer and hematologic malignancies (Hodgkin lymphoma, non-Hodgkin lymphoma, and leukemia), which constitute the most frequent indications for fertility preservation. Chemotherapy, radiotherapy, surgery, or a combination of these treatments can induce ovarian failure requiring fertility preservation prior to treatment. Another important group seeking fertility preservation
Keywords: Fertility preservation; Infertility management